Assessing patient experiences with a Virtual Triage and Assessment Centre (VTAC): a mixed-methods study using an online survey and semi-structured interviews in Renfrew County, Ontario - Antoine St-Amant; Cayden Peixoto; Dez Bair-Patel; Martha Heideman; Kayla Menkhorst; Jonathan Fitzsimon (BMC Primary Care)
Abstract Background In March 2020, the Renfrew County Virtual Triage and Assessment Centre (VTAC) was launched as a large-scale, innovative, hybrid healthcare program. VTAC aims to alleviate pressure on emergency departments by providing additional and more equitable access to family physicians and allied health professionals. This study’s objective was to evaluate patients’ experiences with VTAC. Methods In this mixed-methods study, we distributed 3,026 surveys, receiving 383 responses that met our inclusion criteria (13%), and conducted 10 semi-structured interviews with Renfrew County residents aged 18 and above who had utilized VTAC at least once since 2023. Survey data were analyzed through descriptive statistics, chi-squared tests, and a multivariate binary logistic regression, while semi-structured interviews were coded and analyzed using reflexive thematic analysis. Results The majority of survey respondents were aged over 55 (58%), identified as Caucasian (91%) and women (70%), with 76% having college or university-level education. Additionally, 81% were either unattached, or attached to a doctor who was not easily accessible. Our findings demonstrate overall satisfaction with VTAC, with 86% patients reporting that they were satisfied or very satisfied with the program. This was irrespective of demographic characteristics, health status, or appointment modality. In our interviews, four main themes emerged: “Healthcare in Renfrew County”, “Accessing VTAC”, “VTAC Clinical Care”, and “Improving VTAC”. These themes underscore major difficulties residents encounter in accessing healthcare in Renfrew County and illustrate that services from VTAC align with a genuine population-level need, contributing to mitigating some of these challenges. Conclusion Renfrew County, like many other underserved regions, is grappling with a crisis of access to healthcare. VTAC addresses this gap by providing timely access to a family doctor. Our findings demonstrate patient acceptability and satisfaction with VTAC, offering insights that could guide the design of similar healthcare programs. This model may also serve as a scalable solution for improving healthcare access in underserved regions facing similar challenges.